2007
DOI: 10.1016/j.eurpsy.2007.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Body dysmorphic disorder and cosmetic surgery: Evolution of 24 subjects with a minimal defect in appearance 5 years after their request for cosmetic surgery

Abstract: ObjectivesTo evaluate the effect of cosmetic surgery and the stability of body dysmorphic disorder (BDD) diagnosis in patients with a minimal defect in appearance, with and without BDD, 5 years after their request for plastic surgery.Subjects and methodsThirty patients requesting cosmetic surgery with minimal defect in appearance, of whom 12 had BDD and 18 did not, were re-evaluated 5 years later by telephone interview regarding their cosmetic surgery interventions, satisfaction with the intervention, BDD diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(42 citation statements)
references
References 32 publications
0
33
0
9
Order By: Relevance
“…This is probably due to the small sample size of this study. Studies performed by Tignol and Veale also found that BDD patients seeking cosmetic surgery were younger than their non-BDD counterparts but subject groups did not differ in gender [7,15]. These results suggest that surgeons who perform cosmetic rhinoplasty should have a higher index of suspicion in young patients seeking cosmetic rhinoplasty with a minimal defect in appearance.…”
Section: Discussionmentioning
confidence: 60%
“…This is probably due to the small sample size of this study. Studies performed by Tignol and Veale also found that BDD patients seeking cosmetic surgery were younger than their non-BDD counterparts but subject groups did not differ in gender [7,15]. These results suggest that surgeons who perform cosmetic rhinoplasty should have a higher index of suspicion in young patients seeking cosmetic rhinoplasty with a minimal defect in appearance.…”
Section: Discussionmentioning
confidence: 60%
“…7 Individuals with BDD may receive unnecessary dermatological procedures and cosmetic surgeries, which waste resources by failing to address the underlying problem. [10][11][12] BDD may present in young people as well as is adults. However, in young people BDD is thought to present on more of a continuum from normal adolescent selfconsciousness.…”
Section: Introductionmentioning
confidence: 99%
“…Prospektivna studija Tignol i sar. [37] pacijenata sa minimalnim telesnim manama koji su se podvrgli hiruškim zahvatima ukazala je da kozmetska hirurgija nije imala efikasnost na telesni dismorfički poremećaj, stepen hendikepa ili komorbiditet. Sa druge strane, jednogodišnje praće-nje Felix i sar.…”
Section: Estetske Hirurške Intervencije Kod Pacijenara Sa Telesnim DIunclassified